Physiology of the autonomic nervous system: a guided revision - Abdullah, Aszrin (Malaysian Integrated Medical Professionals Association, 2024)
This book is designed as a revision tool that provides concise yet comprehensive coverage of essential information. All content has been carefully checked and reviewed to ensure accuracy at the time of publication. However, as medicine is an ever-evolving field, the knowledge presented may expand or change over time. Therefore, readers are encouraged to verify any information they find in this book with other sources, especially if discrepancies arise.